A historical review of energy topics in German geographical literature from 1950 to 2008 - Schüssler, Frank (ERDKUNDE, 2009)
The article quantitatively and qualitatively evaluates German textbooks and articles in popular German geography journals, discussing patterns of local and thematic tendencies. The analysis shows a growing number of articles on renewable energy, while fossil and nuclear fuels are continuously discussed. Energy plays a minor role in German textbooks, while it is a persisting issue in journals. Nonetheless, a structured energy discussion is hardly visible in geographical journals; instead a large variety of single, unconnected papers has been published. A common theoretical framework does not exist in geographical energy research. As a result, current energy questions are not connected with geography, although geography can massively contribute to the challenges of climate change and decreasing fossil resources.